Fotossensibilização de biofilmes formados em resinas para base de prótese – in vitro - Gomes, Carlos Eduardo de Albuquerque (2012)
This study evaluated the effect of PDT (Photodynamic Therapy) against Streptococcus mutans, Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Candida albicans biofilms formed on the surface of acrylic resin specimens. Methods: The PDT consisted in the application of 0.05% methylene blue on the specimens, associated to irradiation with a light-emitting diode (LED) of 630nm and 150mW. The energy doses provided by the LED were set to 10 (a) and 30 (b) J/cm2. For each microorganism, the biofilm formation occurred during immersion of the specimens in a culture medium broth containing 106 colony-forming units (CFU)/ml for 48 hours at 37°C. But, at first, the specimens were sterilized in ethylene oxide gas and randomly divided into groups (n=5): experimental (PDT a,b), which were contaminated, stained and irradiated with the different doses of energy; control 1, only contaminated; control 2, contaminated, stained and not irradiated; control 3 (a,b), contaminated, not stained and irradiated; control 4, not contaminated, not stained and not irradiated. Afterward, the specimens were submitted to contact with culture medium agar for 10 minutes, in separated Petri plates, which were incubated for 48 hours at 37°C. The number of CFU was obtained, and the data were expressed according to scores (1=0; 2=1-10; 3=11-100; 4=101-1000; 5>1000) and analyzed by Kruskall Wallis and Dunn tests (α=0.05). Results: S. mutans was only sensitized by the dye; P. aeruginosa and C. albicans were also sensitized by the dye, but showed a CFU reduction to score 2 by PDTb; S. aureus and E. coli, presented an initial score of 3 and achieved a CFU reduction to score 2 by PDTb (p<0.05). Conclusion: PDT was effective in disinfection of acrylic resin specimens and the effectiveness varied according to the dose of energy of the LEDs.